PTU-138 A randomised controlled trial of six weeks of home enteral nutrition versus standard care after oesophagectomy or total gastrectomy for cancer: report on a pilot and feasibility study. (22nd June 2015) - Bowrey, D; Baker, M; Halliday, V; Thomas, A; Pulikottil-Jacob, R; Smith, K; Morris, T; Ring, A
Abstract : Introduction: Poor nutrition in the first months after oesophagogastric resection may be one of the contributing factors to the reduced quality of life seen in these patients. The aim of this pilot and feasibility study was to ascertain the feasibility and potential benefit of home enteral nutrition to inform a subsequent multi-centre randomised controlled trial. Method: Patients undergoing oesophagectomy/total gastrectomy were randomised to either 6 weeks of home jejunostomy feeding (intervention) or treatment as usual (control). The intervention (overnight feeding) provided 50% of energy and protein requirements. Primary outcome measures were recruitment and retention rates at 6 weeks and 6 months. Secondary outcome measures were quality of life, nutritional intake (baseline, hospital discharge, 6 weeks post hospital discharge, 3 and 6 months postoperatively) and healthcare costs. Purposive sampling of patients enrolled in the study was conducted so that interviews could be conducted with patient participants and their informal carers, in order to ascertain experiences of living with a jejunostomy tube and home feeding. Results: 54 of 112 (48%) eligible patients participated in the study over the 20 months. Study retention at six weeks was 41/54 patients (76%) and at six months was 36/54 (67%). Operations were oesophagectomy (32 patients) and total gastrectomy (9 patients). Seventeen of the 20 participants (85%) in the intervention group received treatment as planned, while eight of the 21 (38%) participants in the control arm required rescue home enteral feeding. The pooled estimate of standard deviation for the EORTC QLQ C30 tool was 23 at three months after surgery, and for the OG25 tool, it was 15. The economic evaluation suggested that the mean healthcare costs associated with intervention were slightly less than usual treatment. The interview study revealed that participants described coping mechanisms for managing the feeding tube and high levels of compliance with both tube care and the feeding regimen. Conclusion: In this pilot and feasibility study 90% of the target sample size was recruited, 48% of the eligible population, with a retention rate of 67% at six months. The intervention was acceptable to the participants. A large scale multi-centre study to fully evaluate this intervention should be feasible. Disclosure of interest: D. Bowrey Grant/ Research Support from: Nutricia, Fresenius-Kabi, M. Baker: None Declared, V. Halliday: None Declared, A. Thomas Grant/ Research Support from: Fresenius-Kabi, R. Pulikottil-Jacob: None Declared, K. Smith: None Declared, T. Morris: None Declared, A. Ring: None Declared.